Influence of Quantum Learning on Interest in Reading and Cognitive Ability in History Subject of SMA Negeri 9 Palu Students - A Sehe, Latif; Juraid, Juraid; Misnah, Misnah (Journal of Education Method and Learning Strategy, 2025)
Currently, students' interest in reading in Indonesia has not experienced a significant increase, even though the government has tried to make improvements from year to year. Formulation problem in this study: How does the quantum learning model influence students' interest in reading history? Influence model quantum learning learning on students' cognitive abilities in history subjects. Research objectives: To analyze the influence of the quantum learning model on students' reading interest in history subjects and to analyze the influence of the quantum learning model on students' cognitive abilities in history subjects. Research methods: This type of research is a quasi-experiment, a research that is almost similar to an experiment but not entirely an experiment because the research subjects cannot be manipulated and controlled intensively. Research results: The interpretation of these data may reflect the success of the program or strategy implemented to improve cognitive abilities. However, further analysis is needed to identify these factors in order to draw more valid conclusions regarding the effectiveness of the intervention and inform future decision-making.